Neurological Findings and a Brief Review of the Current Literature in a Severe Case of Aicardi-Goutières Syndrome Due to an IFIH1 Mutation - Železnik, Mojca; Vesnaver, Tina Vipotnik; Neubauer, David; Soltirovska-Šalamon, Aneta (Neuropediatrics, 2024)
Aicardi-Goutières syndrome (AGS) is a rare genetic early-onset progressive encephalopathy with variable clinical manifestations. The IFIH1 mutation has been confirmed to be responsible for type I interferon production and activation of the Janus kinase signaling pathway. We herein stress neurological observations and neuroimaging findings in a severe case report of an infant with AGS type 7 due to an IFIH1 mutation who was diagnosed in the first month of life. We also review neurological characteristics of IFIH1 mutations through recent literature.
Keywords: Aicardi-Goutières syndrome; IFIH1; type I interfernopathy; calcifying encephalopathy